2021
DOI: 10.3748/wjg.v27.i22.3050
|View full text |Cite
|
Sign up to set email alerts
|

Current approach to treatment of minimal hepatic encephalopathy in patients with liver cirrhosis

Abstract: Minimal hepatic encephalopathy (MHE) corresponds to the earliest stage of hepatic encephalopathy (HE). MHE does not present clinically detectable neurological-psychiatric abnormalities but is characterized by imperceptible neurocognitive alterations detected during routine clinical examination via neuropsychological or psychometrical tests. MHE may affect daily activities and reduce job performance and quality of life. MHE can increase the risk of accidents and may develop into overt enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
0
11
0
1
Order By: Relevance
“…Lactulose is often used in MHE clinical treatment. The mechanism is that lactulose is not absorbed in the human intestine and concurrently decomposes and releases lactic acid and acetic acid, acidifying the intestinal tract and promoting colon peristalsis as well as content excretion, which can alleviate the disease to some extent but cannot completely cure it [13]. Thus, its therapeutic effect needs further improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Lactulose is often used in MHE clinical treatment. The mechanism is that lactulose is not absorbed in the human intestine and concurrently decomposes and releases lactic acid and acetic acid, acidifying the intestinal tract and promoting colon peristalsis as well as content excretion, which can alleviate the disease to some extent but cannot completely cure it [13]. Thus, its therapeutic effect needs further improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In studies comparing probiotics with lactulose, better results were obtained in the NCT test in the lactulose treatment group compared to the probiotic treatment group. 23,24 In another study evaluating the efficacy of probiotics in the treatment of MHE, it was found that Clostridium butyricum and Bifidobacterium infantis were effective in improving MHE in patients with cirrhosis due to HBV. 25 In the prospective study conducted by Goyal et al 26 after 3 months of rifaximin and lactulose treatment of patients with MHE, a significant improvement was found in MHE.…”
Section: Discussionmentioning
confidence: 99%
“…Rifaximin is an antibiotic that is minimally absorbed, has broad-spectrum activity against gram-positive and gram-negative aerobic and anaerobic enteric bacteria, and is clinically available for hepatic encephalopathy or travelers’ diarrhea[ 20 , 21 ]. Our recent clinical studies have elucidated that rifaximin significantly decreased serum endotoxin activity and potentially improved intestinal permeability without modifying the gut microbiome in patients with cirrhosis[ 22 ].…”
Section: Introductionmentioning
confidence: 99%